A $\mathcal {M}\gtrsim 3$ shock in 'El Gordo' cluster and the origin of the radio relic. Issue 2 (19th August 2016) - Botteon, A.; Gastaldello, F.; Brunetti, G.; Kale, R.
Abstract: We present an X-ray and radio study of the famous 'El Gordo', a massive and distant ( z  = 0.87) galaxy cluster. In the deep (340 ks) Chandra observation, the cluster appears with an elongated and cometary morphology, a sign of its current merging state. The GMRT radio observations at 610 MHz confirm the presence of a radio halo, which remarkably overlaps the X-ray cluster emission and connects a couple of radio relics. We detect a strong shock ($\mathcal {M}\gtrsim 3$ ) in the NW periphery of the cluster, co-spatially located with the radio relic. This is the most distant ( z  = 0.87) and one of the strongest shocks detected in a galaxy cluster. This work supports the relic–shock connection and allows us to investigate the origin of these radio sources in an uncommon regime of $\mathcal {M}\gtrsim 3$ . For this particular case we found that shock acceleration from the thermal pool is still a viable possibility.